1997
DOI: 10.1111/j.1439-0418.1997.tb01394.x
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal of Trichogramma platneri Nagarkatti (Hym., Trichogrammatidae) from point‐source releases in an apple orchard in California

Abstract: Egg parasitoids of the genus Trichogramma are commonly released in inundative biological control programmes for lepidopteran pests in a range of cropping systems. In this study we evaluated the dispersal of Trichogramma platneri from a central release point in an apple orchard in relation to time and the number of parasitoids released. Dispersal was monitored by parasitism of codling moth eggs from an insectary culture-used as sentinel eggs. Higher release rates of T. platneri resulted in greater parasitism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 12 publications
2
23
0
Order By: Relevance
“…Parasitism activity declined gradually in the neighboring releasing rows from the releasing point. These results are in agreement with McDougall and Mills (1997) who found that T. platneri released in apple orchards provided less than 10% parasitism of sentinel egg masses 14 m away from the release point. Also, Smith (1988) found that T. minutum parasitism declined with distance from a release point.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Parasitism activity declined gradually in the neighboring releasing rows from the releasing point. These results are in agreement with McDougall and Mills (1997) who found that T. platneri released in apple orchards provided less than 10% parasitism of sentinel egg masses 14 m away from the release point. Also, Smith (1988) found that T. minutum parasitism declined with distance from a release point.…”
Section: Discussionsupporting
confidence: 93%
“…One of the prime considerations in the development of biological control is that the potential agent should have pronounced host-searching and dispersal abilities (McDougall and Mills 1997). Searching vigor in many Trichogramma species has evidently constrained the use of this genus in biological control.…”
Section: Introductionmentioning
confidence: 99%
“…Low dispersal rates in augmentative biological control can lead to attack rates that are high adjacent to release sites but decline rapidly with distance from the release site, as has been found in some Trichogramma parasitoids (e.g., Andow and Prokrym 1991; Greatti and Zandigiacomo 1995;McDougall and Mills 1997;Fournier and Boivin 2000). Wright et al (2001) found that T. ostriniae dispersed substantially farther than other Trichogramma species do without emigrating from fields and interpreted this (correctly in our opinion) as a positive attribute of the species for biological control.…”
Section: Too Little Dispersalsupporting
confidence: 70%
“…For classical control agents high dispersal ability is important to ensure that the benefi cial organism becomes well distributed within the release area, and to reduce the number of release points per area and hence costs (Mcdougall and Mills 1997;Wright et al 2001). Th e scientifi c literature on the spread potential of N. typhlocybae in Italy, France and Slovenia was reviewed with regard to the dispersal rate per year and important infl uencing factors such as habitat structure and anthropogenic infl uence to make predictions for the dispersal of N. typhlocybae in the target regions in austria.…”
Section: Probability Of Spreadmentioning
confidence: 99%